Mulatto Bodies and the Body of Christ - Nathaniel Jung-Chul Lee (Black Theology Papers Project)
Ten years ago, in an article for The Christian Century, theologian Jonathan Tran heralded the work of three black theologians J. Kameron Carter, Willie J. Jennings, and Brian Bantum as inaugurating a “new black theology.” According to Tran, these three thinkers represented “ a major theological shift that [would] if taken as seriously as it deserve[d] change the face not only of black theol ogy but theology as a whole.” Now that ten years have passed, this paper asks: Has it? And arguing that it has not, I offer reflections on why it has not. At the center of my argument will be a critique of the way Carter and Bantum offered their revised un derstanding of racial identity and hybridity by reimagining the identity Jesus through mulatto/a bodies and persons. This, I will claim, is a dead end. It is a project that fails to do the very thing it sets out to do, and ultimately, collapses in on itsel f. My aim in making this critique is less refutation and more redirection. More specifically, I will hope to resolve some of the problematic impulses in their appeal to mulatto identity, and in so doing, clear the way for a new direction in Black Theology.